Pembuatan Masterplan Kawasan Pusat Produksi Benih dan Induk Ikan Lokal di Desa Buko Poso, Way Serdang, Mesuji, Lampung - Nurussalam, Wildan; Supriyono, Eddy; Jariyah, I’it Rohmatul; Mahmud, Moh Burhanuddin (Universitas Batangahari Jambi, 2024)
Kabupaten Mesuji has many rivers, canals, reservoirs, and swamps that can be utilized as facilities for the development of fisheries. However, the level of fish production still relies on catches, which can result in reducing the availability and population of fish. The objective of this research is to create a master plan for establishing a center for local fish seed and broodstock production, considering the land suitability in Buko Poso Village, Way Serdang Sub-district, Mesuji District, Lampung Province. Field observation activities include in-situ and ex-situ water quality measurements at four observation stations, soil sampling at five points with three. The results of the soil texture analysis using the soil triangle indicate clay-textured soil. The suitable species for cultivation include Asian Redtail Catfish, Striped Snakehead, Clown Knifefish, Hoven's Carp, and Nile Tilapia. Infrastructure that can be built includes filter tank ponds, wastewater treatment plants, hatcheries, nursery ponds, broodstock maintenance ponds, breeding ponds, and other supporting facilities.